2012
DOI: 10.1021/ja3049223
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Kinetic Characterization of a Highly Reactive Heme–Thiolate Peroxygenase Compound I

Abstract: The extracellular heme-thiolate peroxygenase from Agrocybe aegerita (AaeAPO) has been shown to hydroxylate alkanes and numerous other substrates using hydrogen peroxide as the terminal oxidant. We describe the kinetics of formation and decomposition of AaeAPO compound I upon its reaction with mCPBA. The UV–vis spectral features of AaeAPO–I (361, 694 nm) are similar to those of chloroperoxidase–I and the recently–described cytochrome P450–I. The second–order rate constant for AaeAPO–I formation was 1.0 (±0.4) ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
122
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 37 publications
13
122
0
Order By: Relevance
“…An observed 2 H KIE for Ole-I decay at this H 2 O 2 concentration, which represents a lower limit for the unmasked value, is provided by a ratio of the fast RRTs, [ H k app / D k app = RRT 1 (H 39 -EA)/RRT 1 (D 39 -EA)], giving a KIE ≥ 8.1 ± 1.1. The large KIE, which has not been previously measured for a P450-I generated with a bound substrate, is in accord with unmasked KIEs for steady-state P450 hydroxylations (12), rapid mixing studies of P450-I (10), and similar thiolateligated heme iron−oxo species (41), and theoretical considerations (43). This confirms that the distinctive C−Cα cleavage catalyzed by OleT most likely commences in a very similar way to P450 monooxygenations.…”
Section: Significancesupporting
confidence: 77%
See 1 more Smart Citation
“…An observed 2 H KIE for Ole-I decay at this H 2 O 2 concentration, which represents a lower limit for the unmasked value, is provided by a ratio of the fast RRTs, [ H k app / D k app = RRT 1 (H 39 -EA)/RRT 1 (D 39 -EA)], giving a KIE ≥ 8.1 ± 1.1. The large KIE, which has not been previously measured for a P450-I generated with a bound substrate, is in accord with unmasked KIEs for steady-state P450 hydroxylations (12), rapid mixing studies of P450-I (10), and similar thiolateligated heme iron−oxo species (41), and theoretical considerations (43). This confirms that the distinctive C−Cα cleavage catalyzed by OleT most likely commences in a very similar way to P450 monooxygenations.…”
Section: Significancesupporting
confidence: 77%
“…The observation of a compound I species in OleT, optically indistinguishable from those that promote hydroxylations (10,41) (Table S1 and Fig. S1A).…”
Section: Significancementioning
confidence: 91%
“…Accordingly, we anticipated that these water-soluble nitroxyl radicals might be able to reduce APO-I readily but would not reduce APO-II efficiently. Furthermore, since cyclohexane carboxylic acid was found to be an excellent substrate for APO (29), the similar molecular topographies of 4-carboxy-TEMPO and 3-carboxy-PROXYL suggested that they would fit into the relatively small, conical active site of APO (25). We tested the reaction of 3-carboxy-PROXYL with the well-studied enzyme CPO in a single-turnover experiment.…”
Section: Significancementioning
confidence: 99%
“…We have recently shown that the APO from Agrocybe aegerita (AaeAPO) forms an oxoiron(IV) porphyrin radical cation (APO-I) that can be detected by UV-visible (UV-vis) spectroscopy (29). This intermediate was shown to be highly competent for the hydroxylation of even strong C−H bonds.…”
mentioning
confidence: 99%
“…They constitute a distinct (super)family of fungal heme‐thiolate proteins that catalyze efficient and selective oxygen‐transfer from peroxides to diverse organic substrates including non‐activated compounds 11. UPOs are relatively stable and versatile biocatalysts, and combine the catalytic cycle of heme peroxidases with the “peroxide shunt” of P450s 12, 13. The first UPO was discovered in the wood‐dwelling agaric fungus Agrocybe aegerita ( Aae UPO); two similar enzymes were described in the mushrooms Coprinellus radians ( Cra UPO) and Marasmius rotula ( Mro UPO) 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%